The Efficacy of the Self in Adonis's Autobiography "Here You Are, O Time - Radwan, Laila Shaaban; Al-Hassan, Haifa (Journal of Ecohumanism, 2025)
Adonis wrote his autobiography entitled "Here You Are, O Time" after the concept of modernity had matured in his mind and his critical project had become clear. He aimed to re-evaluate the past from the perspective of the present to demonstrate what he had accomplished for the revival of poetry and to affirm the correctness of his critical vision despite the multitude of his adversaries and enemies. As one of the poets and thinkers who took upon themselves the task of renewing Arabic poetry, he depicted in his autobiography an image of his self about itself, valuing the actions and stances it had taken, with an overwhelming sense of the self's distinction, uniqueness, and superiority over others. This study examines the efficacy of this self in Adonis's autobiography, which appears prominently with an unparalleled status, undertaking significant tasks and overcoming all the obstacles it faced. This granted it an awareness of the value of its achievements, becoming a voice that overshadowed other voices, remaining unique in undertaking the mission of rescuing poetry from decline. Therefore, all elements of the autobiography revolved around it, and other topics branched from it, extending beyond the scope of depicting the self to portraying its relationship with the other